ANALISIS KINERJA KEUANGAN SEBELUM DAN SELAMA PANDEMI COVID-19 PADA PERUSAHAAN PENERBANGAN PT. GARUDA INDONESIA TBK PADA TAHUN 2017-2022 - Novegya Ratih Primandari; Mailani - Rabiulkhri; Ulandari - Ulandari (Universitas Madura, 2024)
At the Aviation Company PT. Garuda Indonesia Tbk 2017-2022 Period. The analytical method used in this research was the Paired T Test. Apart from that, this research also carried out an independent sample t test. The type of data used in this research was secondary data obtained from the company's official website (www.garuda-indonesia.com). From the results of tests carried out on this research, it was known that the Financial Performance of PT. Garuda Indonesia Tbk Before and During the Covid-19 Pandemic in terms of Liquidity Ratios, Solvency Ratios, Profitability Ratios, Activity Ratios, the company had better performance before the Covid-19 pandemic.